Killer view - Johansen, Roy (Johansen, Iris Kendra Michaels series., 2022)
Hired by an incarceration consultant, who prepares wealthy people for prison, to find his missing partner, army vet and former bodyguard for the rich and famous Jessie Mercado learns just how far someone will go to keep the fate of one man hidden.